Pengaruh Independensi, Kompetensi, dan Partisipasi Dewan Komisaris terhadap Kinerja Keuangan Perusahaan - Feilicia Octosiva; Meilisa Theresia; Athalia Ariati Hidayat (Studi Akuntansi dan Keuangan Indonesia, 2018)
According to the Asian Development Bank report, responsibility of the board is one of the principles that has not been implemented properly in Indonesia. There are several things that can represent the responsibilities of the board such as independency, competence, and participation. The aim to this study is to analyze the effect of the independency proxied by the proportion of independent commissioners, the competence proxied by the board’s working experience in the major industry of the company, and the participation proxied by the average percentage attendance of the board in the meeting to corporate financial performance represented with ROA. The sample used in this study is in the period of 2011-2015 with a total of 1229 firm-years. The hypothesis testing in this research uses panel data regression analysis. The result shows that independency of the board has no effect on corporate financial performance, while the competence of the board has a positive effect on corporate financial performance and participation of the board shows a negative effect on corporate financial performance. Keywords: Competence, corporate financial performance, Independency, participation https://doi.org/10.21632/saki.1.2.158-203